2018
DOI: 10.1038/s41598-018-19776-2
|View full text |Cite
|
Sign up to set email alerts
|

Downy mildew symptoms on grapevines can be reduced by volatile organic compounds of resistant genotypes

Abstract: Volatile organic compounds (VOCs) play a crucial role in the communication of plants with other organisms and are possible mediators of plant defence against phytopathogens. Although the role of non-volatile secondary metabolites has been largely characterised in resistant genotypes, the contribution of VOCs to grapevine defence mechanisms against downy mildew (caused by Plasmopara viticola) has not yet been investigated. In this study, more than 50 VOCs from grapevine leaves were annotated/identified by heads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 69 publications
1
62
0
3
Order By: Relevance
“…Lastly, volatile antibiotics may also be in play. Atta and Acromyrmex ants are known to produce volatile chemicals with antibiotic properties in their mandibular glands, and volatile molecules, including some produced by ants, have been shown to inhibit the development of downy mildew Plasmapara viticola on grapewine (Lazazzara et al 2018). In conclusion, mechanical mechanisms seem highly plausible, and pathways by which antibiotics may travel from ants to plants are multiple.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, volatile antibiotics may also be in play. Atta and Acromyrmex ants are known to produce volatile chemicals with antibiotic properties in their mandibular glands, and volatile molecules, including some produced by ants, have been shown to inhibit the development of downy mildew Plasmapara viticola on grapewine (Lazazzara et al 2018). In conclusion, mechanical mechanisms seem highly plausible, and pathways by which antibiotics may travel from ants to plants are multiple.…”
Section: Discussionmentioning
confidence: 99%
“…Além desses efeitos proporcionados pelo OEP, ressalta-se que esse óleo essencial apresenta volatilização lenta, o que permite a formação de envelopes de proteção sobre o tecido vegetal (Lazazzara et al, 2018), fato que, possivelmente, protegeu os frutos de uvas 'Rubi'.…”
Section: Resultsunclassified
“…Resultados referentes aos voláteis eliminados pelo OEP podem-se relacionar com a capacidade de seus compostos em causar alterações degenerativas nas hifas, acarretando aumento nos vacúolos, elevado número de peroxissomos e de mitocôndrias nas células fúngicas, e perda da integridade da membrana plasmática (Pârvu et al, 2013;Shao et al, 2013 naturalmente emitem compostos voláteis ricos em monoterpenos e sesquiterpenos. Videiras resistentes ao Plasmopara viticola liberam, principalmente muroleno, cariofileno e germacreno B, como forma de proteção (Lazazzara et al, 2018). Esses compostos são encontrados no OEP e em OEG, os quais, possivelmente, foram os responsáveis pela redução do mofo cinzento nas bagas de uva 'Rubi'.…”
Section: Methodsunclassified
“…At the molecular level, resistant hosts react in many different ways after infection has started. Localized callose deposition (Kortekamp et al, 1997;Gindro et al, 2003), volatile organic compounds (Lazazzara et al, 2018), accumulation of secondary metabolites (Figueiredo et al, 2008;Chang et al, 2011), and hypersensitive reaction (HR) (Kortekamp et al, 1997;Gindro et al, 2003;Casagrande et al, 2011) have been reported as important mechanisms to avoid downy mildew infection. Strong expression of defense-related genes has been reported as well from resistant hosts (Polesani et al, 2010;Figueiredo et al, 2012) early after their contact with the oomycete.…”
Section: Infection/resistance Mechanismsmentioning
confidence: 99%